Integration of Social and Emotional Learning (SEL) in Indonesian Elementary Schools: Literature Review - Salsabila, Helga; Saputri, Rizqi Rahmadhani; Asyari, Aisyah Putri; Wibowo, Agus Mukti; Pusposari, Luthfiya Fathi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3780, 2025)
Social and Emotional Learning (SEL) at the elementary education level is important for supporting the development of students' social and emotional skills. This study aims to explore the strategies and challenges of integrating SEL into thematic learning in elementary schools. This study uses a qualitative approach through a literature review, which includes an analysis of various studies related to the application of SEL. The results show that the integration of SEL not only improves students' social and emotional skills but also contributes to academic success. However, challenges such as time constraints, teacher readiness, and stakeholder support remain obstacles to its implementation. This study emphasizes the importance of developing comprehensive education policies and continuous training for teachers to ensure the effectiveness of SEL implementation. Thus, social-emotional learning is expected to strengthen students' character and prepare them to face future challenges.